The Concept of Holistic Education and Its Implementation in the Indonesian Education System (Adabiyah: Jurnal Pendidikan Islam, 2017)
This research has several objectives, the first is to know the meaning of holistic education according to Muchlas Samani. And the second is to know the implementation of holistic education on education system in Indonesia according to Muchlas Samani. This research is a historical research with a kind of biography. Data analysis used by researcher in this research is (1) review all data obtained from research about concept and practice of holistic education according to Muchlas Samani's thought, (2) to further reduce the data, (4) hereinafter the data collected and arranged according to the required category, (5) at the last stage, the researcher does the meaning of the research result obtained with the sentence which is easy to understand and still has relevance to the title, the purpose and the formulation of the existing problem. The results obtained from this research is holistic education according Muchlas Samani is a concept of education intact, not partial. What makes the Islamic values as the spirit and the subjects as a container. And has a goal to develop the potency possessed by learners in facing the futurenya. For implementation of holistic education in the education system in Indonesia according to Muchlas Samani is still lacking. This is because in the education system in Indonesia is still using the general curriculum.